The pattern of mucocutaneous disorders in pediatric HIV patients in a tertiary care center - Sanjith Saravanabhavan; Seethalakshmi Ganga Vellaisamy; Kannan Gopalan; Muthusamy Kandasamy (Wolters Kluwer Medknow Publications, 2020)
Background: Dermatological manifestations constitute one of the most common clinical features in HIV-infected children. An early recognition of such features is important for an early diagnosis and also to assess the prognosis of HIV infection. Objective: The present study was conducted to determine the prevalence and pattern of mucocutaneous manifestations in HIV-infected children and also to assess the association between those manifestations and degree of cellular immune deficiency. Materials and Methods: This was a cross-sectional study conducted in the Outpatient Department of SKIN and STD between April 2017 to March 2018. A total of 100 HIV patients <18 years of age were included in the study. After screening, skin diseases were classified under four broad categories: (i) Infectious dermatoses, (ii) inflammatory dermatoses, (iii) neoplastic conditions, and (iv) drug-related dermatoses. Data were coded and analyzed. Results: The prevalence of cutaneous manifestation in our study was found to be 82% among the HIV-infected children. In toto, inflammatory disorders (58%) were more common, followed by nail disorders (40%), infectious dermatoses, (36%) and drug-related conditions (23%). Among the individual disorders, diffuse pigmentation of nails (24%) was the most common condition and zidovudine was the most common implicated drug in 22% of children. Conclusion: Due to antiretroviral therapy (ART), the occurrence of infectious dermatoses has come down, but we are encountering adverse effects due to drugs. Due to the ability of ART to reconstitute the immune system, there have been undoubtedly significant changes in the nature and prevalence of skin disorders.